Tumor-associated tissue eosinophilia predicts favorable clinical outcome in solid tumors: a meta-analysis - Hu, Guoming; Wang, Shimin; Zhong, Kefang; Xu, Feng; Huang, Liming; Chen, Wei; Cheng, Pu (BMC cancer, 2020)
Activated eosinophils have been deemed to affect carcinogenesis and tumor progression via various mechanisms in tumor microenvironment. However, the prognostic role of tumor-associated tissue eosinophilia (TATE) in human cancers remains controversial. Therefore, we conducted this meta-analysis to better comprehend the association between TATE and clinical outcomes of patients. We searched PubMed, Embase and EBSCO to determine the researches assessing the association between TATE and overall survival (OS) and/or disease-free survival (DFS) in patients with cancer, then combined relevant data into hazard ratios (HRs) or odds ratio (OR) for OS, DFS and clinicopathological features including lymph node metastasis etc. with STATA 12.0. Twenty six researches with 6384 patients were included in this meta-analysis. We found that the presence of TATE was significantly associated with improved OS, but not with DFS in all types of cancers. In stratified analyses based on cancer types, pooled results manifested that the infiltration of eosinophils was remarkably associated with better OS in esophageal carcinoma and colorectal cancer. In addition, TATE significantly inversely correlated with lymph node metastasis, tumor stage and lymphatic invasion of cancer. TATE promotes survival in cancer patients, suggesting that it is a valuable prognostic biomarker and clinical application of biological response modifiers or agonists promoting TATE may be the novel therapeutic strategy for patients.